Adopting a Microskills Approach to Teaching Counseling in Communication Sciences and Disorders: Lessons From Counselor Training. - Wofford, Mary Claire; Rosario-Singer, Loidaly G.; De Nardo, Thales (Perspectives of the ASHA Special Interest Groups, 2026)
Purpose: Teaching counseling skills in speech-language pathology is complex and essential for equipping new clinicians to serve individuals with diverse communication needs effectively. This tutorial offers an interdisciplinary educational perspective on using a microskills approach to teach counseling skills in a communication sciences and disorders (CSD) curriculum. Method: In this tutorial, we present an initial discussion of challenges of and opportunities for teaching counseling content in CSD. We define the microskills approach and learn from guiding concepts in counselor education curricula. We offer suggestions for complementary pedagogies from the literature based on CSD education and present applied small-group interactive exercises to practice microskills with preservice clinicians. Finally, we apply the microskills approach to brief clinical scenarios and debrief counseling strategies for person-centered, culturally responsive care. Conclusion: A microskills approach to teaching counseling skills in CSD offers practical and culturally appropriate strategies for emerging clinicians.